Autonomous air, sea, undersea, and land vehicles - Rajesh. S (International Journal on Orange Technologies, 2019)
An autonomous vehicle is one which will drive itself from a start line to a predetermined destination in “autopilot” mode using various in-vehicle technologies and sensors, including adaptive control, active steering (steer by wire), anti-lock braking systems (brake by wire), GPS navigation technology, lasers, and radar. Self-driving vehicles are cars or trucks during which human drivers are never required to require control to securely operate the vehicle. Also referred to as autonomous or “driverless” cars, they combine sensors and software to regulate, navigates, and drives the vehicle